GRP78 Protein Expression in Ovarian Cancer Patients and Perspectives for a Drug-Targeting Approach. (18th March 2012) - Delie, Florence; Petignat, Patrick; Cohen, Marie
Abstract : Glucose-regulated protein of 78 kD (GRP78) is a chaperone protein mainly located in the endoplasmic reticulum (ER). This protein is normally present at low levels in adult cells but its expression is triggered by ER stress including glucose deprivation and hypoxia. In tumor cells, it is overexpressed with fraction of protein found at the cell surface. This paper presents the physiology of GRP78 in the context of ovarian cancer and its potential use as drug delivery systems targeting ovarian cancer cell.